Resection of an aggressive nodular fasciitis of the mandible in an infant girl - Bruno Catoia Fonseca; Luis Velozo Papez; Emilia Barros Becker; Ma Angélica Paulós Parot; Margarita Aldunate Riedemann; Carla Muñoz Torres (Elsevier, 2021)
Nodular fascitis is a benign pseudosarcomatous self-limited fibroblastic and myofibroblastic cell neoplasia that occasionally can be found in pediatric patients, in who head and neck is reported to be a common location. Although nodular fascitis could be suspected by imaging, histologic review is mandatory to certificate the diagnosis and rule out malignant conditions of similar behavior. We report the case of an infant girl with a big, solid, left submandibular mass with a rapidly progressive growth that erodes mandibular body. The diagnosis is proven by histopathology and immunohistochemistry. The lesion does not respond to triamcinolone intralesional infiltration and is finally surgically resected by a transcervical approach with good results and no recurrence at follow-up.